2014
DOI: 10.2337/dc13-2539
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Cost-effectiveness of Continuous Positive Airway Pressure to Manage Obstructive Sleep Apnea in Patients With Type 2 Diabetes in the U.K.

Abstract: OBJECTIVETo assess clinical outcomes and cost-effectiveness of using continuous positive airway pressure (CPAP) to manage obstructive sleep apnea (OSA) in patients with type 2 diabetes (T2D) from the perspective of the U.K.'s National Health Service (NHS). RESEARCH DESIGN AND METHODSUsing a case-control design, 150 CPAP-treated patients with OSA and T2D were randomly selected from The Health Improvement Network (THIN) database (a nationally representative database of patients registered with general practition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 33 publications
0
43
0
1
Order By: Relevance
“…13 Treating OSA in adults using CPAP improves IR, although the impact on glycemia is more unpredictable. 14 In children, the association of OSA with IR and MetSyn has been inconsistent: some studies have found that OSA increases risk of IR 15 and dyslipidemia, 16 whereas others have found that IR and MetSyn are primarily determined by obesity. 17,18 Most studies have examined associations rather than causal relationships.…”
mentioning
confidence: 99%
“…13 Treating OSA in adults using CPAP improves IR, although the impact on glycemia is more unpredictable. 14 In children, the association of OSA with IR and MetSyn has been inconsistent: some studies have found that OSA increases risk of IR 15 and dyslipidemia, 16 whereas others have found that IR and MetSyn are primarily determined by obesity. 17,18 Most studies have examined associations rather than causal relationships.…”
mentioning
confidence: 99%
“…OSA is prevalent among patients with diabetes and may contribute to several important aspects, including glycemic control, hypertension, cardiovascular disease, and microvascular complications (3,4). In our observational study in a clinical setting, patients with type 2 diabetes and untreated OSA developed higher HbA 1c levels (and blood pressure) compared with best-matched patients treated with continuous positive airway pressure (CPAP), despite greater prescription of antidiabetes medications (2). Although data were unavailable, it is likely that the patients studied had significant symptomatic OSA given their BMI and the usual symptom-driven presentation to primary care.…”
mentioning
confidence: 87%
“…A potential association between obstructive sleep apnea (OSA) and diabetes is intriguing, as acknowledged in the commentary by Tahrani (1) on our article (2). OSA is prevalent among patients with diabetes and may contribute to several important aspects, including glycemic control, hypertension, cardiovascular disease, and microvascular complications (3,4).…”
mentioning
confidence: 93%
“…Ефект СРАР-терапії підвищувався зі збіль-шенням прихильності до лікування і був більш вираженим при СОАС середнього та тяжкого ступенів, ожирінні та у випадках погано конт-рольованого діабету [17,46].…”
Section: обговоренняunclassified